2001
DOI: 10.1152/ajplung.2001.281.3.l732
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neutrophil apoptosis by acrolein: a mechanism of tobacco-related lung disease?

Abstract: Cigarette smoking is known to contribute to inflammatory diseases of the respiratory tract by promoting recruitment of inflammatory-immune cells such as neutrophils and perhaps by altering neutrophil functional properties. We investigated whether acrolein, a toxic unsaturated aldehyde found in cigarette smoke, could directly affect neutrophil function. Exposure of freshly isolated human neutrophils to acrolein markedly inhibited spontaneous neutrophil apoptosis as indicated by loss of membrane asymmetry and DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 50 publications
(60 reference statements)
7
67
0
Order By: Relevance
“…We used Annexin V, an anticoagulant protein with high affinity and selectivity for phosphatidylserine (PS), to detect PS exteriorization, and propidium iodide (PI), a membrane impermeable dye, to monitor cell membrane integrity. Consistent with previous reports (8)(9)(10)(11), CSE and nicotine significantly reduced neutrophil spontaneous death. The most significant effects were observed at 36 h and 54 h (Fig.…”
Section: Cse and Nicotine Block Akt Deactivation And Delay Neutrophilsupporting
confidence: 93%
See 1 more Smart Citation
“…We used Annexin V, an anticoagulant protein with high affinity and selectivity for phosphatidylserine (PS), to detect PS exteriorization, and propidium iodide (PI), a membrane impermeable dye, to monitor cell membrane integrity. Consistent with previous reports (8)(9)(10)(11), CSE and nicotine significantly reduced neutrophil spontaneous death. The most significant effects were observed at 36 h and 54 h (Fig.…”
Section: Cse and Nicotine Block Akt Deactivation And Delay Neutrophilsupporting
confidence: 93%
“…Some of the chemical constituents of cigarette smoke (CS), such as nicotine and acrolein, have been shown to directly delay neutrophil spontaneous death (9)(10)(11), providing a mechanism for the massive accumulation of neutrophils in the lungs of smoke-induced COPD patients. Here, we investigate the mechanism by which CS reduces neutrophil spontaneous death.…”
mentioning
confidence: 99%
“…Acrolein can either induce apoptosis [82,125] or have an inhibitory effect on apoptotic pathways as observed for human neutrophils [126]. Acrolein induced apoptosis in human lung epithelial (HBE1) cells at 10-25-μM and in isolated human alveolar macrophages at 25-μM exposure, as indicated by DNA fragmentation after 24 h of exposure.…”
Section: Acrolein Induces Necrotic and Apoptotic Cell Deathmentioning
confidence: 89%
“…Tanel and Averill-Bates [125] have observed during their studies on apoptotic pathways in CHO cells that procaspase-3 was proteolytically processed but that caspase-3 was not catalytically active. Finkelstein et al [126] reported that exposure of human neutrophils to acrolein also prevented the activation of caspase-3. Why can acrolein inactive cas-pases?…”
Section: Acrolein Induces Necrotic and Apoptotic Cell Deathmentioning
confidence: 99%
“…Because most particulate matter is filtered out by the airways, volatile components of the gas phase of smoke are believed to be responsible for changes in enzymatic activity, such as oxidative inhibition of ␣ 1 -antitrypsin (43). Of these, nicotine, acrolein, and acetaldehyde seem to be key short-acting pharmacological agents (44). Interestingly, acrolein stimulates release of inflammatory cytokines and can alter cellular repair processes by impairing fibroblast function (45).…”
Section: Discussionmentioning
confidence: 99%